Characterization of Variability in Toxicokinetics and Toxicodynamics of Tetrachloroethylene Using the Collaborative Cross Mouse Population - Cichocki, Joseph A. (Environ Health Perspect, 2017)
BACKGROUND: Evaluation of interindividual variability is a challenging step in risk assessment. For most environmental pollutants, including perchloroethylene (PERC), experimental data are lacking, resulting in default assumptions being used to account for variability in toxicokinetics and toxicodynamics. OBJECTIVE: We quantitatively examined the relationship between PERC toxicokinetics and toxicodynamics at the population level to test whether individuals with increased oxidative metabolism are be more sensitive to hepatotoxicity following PERC exposure. METHODS: Male mice from 45 strains of the Collaborative Cross (CC) were orally administered a single dose of PERC ([Formula: see text]) or vehicle (Alkamuls-EL620) and euthanized at various time points ([Formula: see text] /strain/time). Concentration–time profiles were generated for PERC and its primary oxidative metabolite trichloroacetate (TCA) in multiple tissues. Toxicodynamic phenotyping was also performed. RESULTS: Significant variability among strains was observed in toxicokinetics of PERC and TCA in every tissue examined. Based on area under the curve (AUC), the range of liver TCA levels spanned nearly an order of magnitude ([Formula: see text]-fold). Expression of liver cytochrome P4502E1 did not correlate with TCA levels. Toxicodynamic phenotyping revealed an effect of PERC on bodyweight loss, induction of peroxisome proliferator activated receptor-alpha (PPAR [Formula: see text])-regulated genes, and dysregulation of hepatic lipid homeostasis. Clustering was observed among a) liver levels of PERC, TCA, and triglycerides; b) TCA levels in liver and kidney; and c) TCA levels in serum, brain, fat, and lung. CONCLUSIONS: Using the CC mouse population model, we have demonstrated a complex and highly variable relationship between PERC and TCA toxicokinetics and toxicodynamics at the population level. https://doi.org/10.1289/EHP788